Preliminary Study on biogas production from POME by DBD plasma - Ariadi Hazmi; Reni Desmiarti; Primas Emeraldi; Muhammad Imran Hamid; Edwardo Edwardo; Eka Putra Waldi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
A new technology to produce biogas using a dielectric barrier discharge (DBD) plasma system from palm oil mill effluent (POME) was investigated. The batch experiments were examined at applied voltages of 15, 20 and 25 kV. The results showed that the highest yields of hydrogen and methane were achieved at an applied voltage of 25 kV after 1 hour were 2.42 and 1.32 mL/mL of POME, respectively. The biogas was composed of 65% hydrogen and 35% methane. In order to make the results of this study applicable to biogas plants, the effects of flowrate and consumed energy are important parameters that should be further investigated in a future study.